The need for weed: marijuana policy & public politics in the criminal justice system - Wallace, Kellie A. (Kendall Hunt Publishing Company, 2022)
"Cannabis is everywhere! Whether you call it weed, pot, or marijuana, cannabis by any other name is still cannabis. From your stereotypical street drug dealer to medical cannabis dispensaries to courtrooms across America, we cannot escape the hot buzz that is weed. While it may be hot, it is nothing new; since being made illegal over a hundred years ago, proponents of its use and benefits have rallied and advocated for its declassification as an illicit substance, upon deaf ears until very recently. Individuals’ states and companies have been making moves to decriminalize and regulate this drug. The ongoing debates and public discourse associated with cannabis legalization have broader implications for criminal justice policy and social equity in the United States. The Need for Weed: Marijuana Policy and Public Politics in the Criminal Justice System address the impact of cannabis policy on crime and policing, as well as its impact on social justice and public policy more broadly."--